Developmental Reprogramming in Mesenchymal Stromal Cells of Human Subjects with Idiopathic Pulmonary Fibrosis - Chanda, Diptiman; Kurundkar, Ashish; Rangarajan, Sunad; Locy, Morgan; Bernard, Karen; Sharma, Nirmal S.; Logsdon, Naomi J.; Liu, Hui; Crossman, David K.; Horowitz, Jeffrey C.; De Langhe, Stijn; Thannickal, Victor J. (Scientific reports, 2016)
Cellular plasticity and de-differentiation are hallmarks of tissue/organ regenerative capacity in diverse species. Despite a more restricted capacity for regeneration, humans with age-related chronic diseases, such as cancer and fibrosis, show evidence of a recapitulation of developmental gene programs. We have previously identified a resident population of mesenchymal stromal cells (MSCs) in the terminal airways-alveoli by bronchoalveolar lavage (BAL) of human adult lungs. In this study, we characterized MSCs from BAL of patients with stable and progressive idiopathic pulmonary fibrosis (IPF), defined as <5% and ≥10% decline, respectively, in forced vital capacity over the preceding 6-month period. Gene expression profiles of MSCs from IPF subjects with progressive disease were enriched for genes regulating lung development. Most notably, genes regulating early tissue patterning and branching morphogenesis were differentially regulated. Network interactive modeling of a set of these genes indicated central roles for TGF-β and SHH signaling. Importantly, fibroblast growth factor-10 (FGF-10) was markedly suppressed in IPF subjects with progressive disease, and both TGF-β1 and SHH signaling were identified as critical mediators of this effect in MSCs. These findings support the concept of developmental gene re-activation in IPF, and FGF-10 deficiency as a potentially critical factor in disease progression.